The Roles of Blood Lipid-Metabolism Genes in Immune Infiltration Could Promote the Development of IDD - Li, Weihang; Ding, Ziyi; Zhang, Huan; Shi, Quan; Wang, Dong; Zhang, Shilei; Xu, Songjie; Gao, Bo; Yan, Ming (Frontiers in Cell and Developmental Biology, 2022)
Objectives: Intervertebral disc degeneration is a progressive and chronic disease, usually manifesting as low back pain. This study aimed to screen effective biomarkers for medical practice as well as figuring out immune infiltration situations between circulation and intervertebral discs. Methods: Gene expression profiles of GSE124272 was included for differentially analysis, WGCNA and immune infiltration analysis from GEO database, and other GSE series were used as validation datasets. A series of validation methods were conducted to verify the robustness of hub genes, such as principal component analysis, machine learning models, and expression verification. Lastly, nomogram was established for medical practice. Results: 10 genes were commonly screened via combination of DEGs, WGCNA analysis and lipid metabolism related genes. Furthermore, 3 hub gens CYP27A1, FAR2, CYP1B1 were chosen for subsequent analysis based on validation of different methods. GSEA analysis discovered that neutrophil extracellular traps formation and NOD-like receptor signaling pathway was activated during IDD. Immune infiltration analysis demonstrated that the imbalance of neutrophils and γδT cells were significantly correlated with IDD progression. Nomogram was established based on CYP27A1, FAR2, CYP1B1 and age, the calibration plot confirmed the stability of our model. Conclusion: CYP27A1, FAR2, CYP1B1 were considered as hub lipid metabolism related genes (LMRGs) in the development of IDD, which were regarded as candidate diagnostic biomarkers especially in circulation. The effects are worth expected in the early diagnosis of IDD through detecting these genes in blood.